Anticancer effect of zinc oxide nanoparticles prepared by varying entry time of ion carriers against A431 skin cancer cells in vitro - Aljohar, Albandri Yousef; Muteeb, Ghazala; Zia, Qamar; Siddiqui, Sahabjada; Aatif, Mohammad; Farhan, Mohd; Khan, Mohd. Farhan; Alsultan, Abdulrahman; Jamal, Azfar; Alshoaibi, Adil; Ahmad, Ejaz; Alam, Mir Waqas; et al. (Frontiers in Chemistry, 2022)
Although, zinc oxide nanoparticles (ZRTs) as an anti-cancer agent have been the subject of numerous studies, none of the reports has investigated the impact of the reaction entry time of ion-carriers on the preparation of ZRTs. Therefore, we synthesized variants of ZRTs by extending the entry time of NaOH (that acts as a carrier of hydroxyl ions) in the reaction mixture. The anti-proliferative action, morphological changes, reactive oxygen species (ROS) production, and nuclear apoptosis of ZRTs on human A431 skin carcinoma cells were observed. The samples revealed crystallinity and purity by X-ray diffraction (XRD). Scanning electron microscopy (SEM) images of ZRT-1 (5 min ion carrier entry) and ZRT-2 (10 min ion carrier entry) revealed microtubule like morphology. On prolonging the entry time for ion carrier (NaOH) introduction in the reaction mixture, a relative ascent in the aspect ratio was seen. The typical ZnO band with a slight shift in the absorption maxima was evident with UV-visible spectroscopy. Both ZRT-1 and ZRT-2 exhibited non-toxic behavior as evident by RBC lysis assay. Additionally, ZRT-2 showed better anti-cancer potential against A431 cells as seen by MTT assay, ROS generation and chromatin condensation analyses. At 25 μM of ZRT-2, 5.56% cells were viable in MTT test, ROS production was enhanced to 166.71%, while 33.0% of apoptotic cells were observed. The IC50 for ZRT-2 was slightly lower (6 μM) than that for ZRT-1 (8 μM) against A431 cells. In conclusion, this paper presents a modest, economical procedure to generate ZRT nano-structures exhibiting strong cytotoxicity against the A431 cell line, indicating that ZRTs may have application in combating cancer.